2020
DOI: 10.33087/dikdaya.v10i2.172
|View full text |Cite
|
Sign up to set email alerts
|

Efektivitas Penggunaan Media Poster dalam Pembelajaran Keterampilan Berbicara Biografi Pada Siswa Kelas VII SMP Negeri 18 Kota Jambi

Abstract: This study aims to determine: (1) the differences in learning achievement of speaking skills in Biography between class VII students of SMP Negeri 18 Jambi City who were taught using poster media with students who were taught without using poster media; (2) the effectiveness of poster media in learning biography on speaking skills of class VII SMP Negeri 18 Jambi City. This research is a quasi experimental study. The research design was a pre-test and post test group. The subjects in this study were all grade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Media are all forms of intermediaries that are used by all humans to convey ideas, ideas or opinions so that the ideas, ideas or opinions expressed reach the intended recipient (Enawaty and Sari, 2010). Media has several advantages, including making abstract and complex concepts into something real, simple, systematic and clear (Wahyuni et al, 2015). Learning Media is a tool that is used as an intermediary for teachers in conveying information to students (Fitri and Ismulyati, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Media are all forms of intermediaries that are used by all humans to convey ideas, ideas or opinions so that the ideas, ideas or opinions expressed reach the intended recipient (Enawaty and Sari, 2010). Media has several advantages, including making abstract and complex concepts into something real, simple, systematic and clear (Wahyuni et al, 2015). Learning Media is a tool that is used as an intermediary for teachers in conveying information to students (Fitri and Ismulyati, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Based on research conducted by Asmara (2015), it shows that learning using audiovisual media is more successful than learning without media. Then research by Fujiyanto et al (2016) showed that the use of audio-visual media can help understand abstract material into concrete and can improve student learning outcomes, Further, research by Wahyuni et al (2015) showed that students who were taught using audio-visual media had an average learning interest higher than students who were taught without media.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research conducted by Wahyuni et al (2015), it was found that the level of understanding of students at SMPN 2 Sulang in Rembang on Energy in Living Systems topic was still relatively low with a percentage of only 45% of the 132 students who graduated from the Minimum Completeness Criteria, which was 75. This was apparently due to the use of a teachercentered lecture model and textbooks so that the material explained is still abstract.…”
Section: Introductionmentioning
confidence: 90%